Effects of Brief UV-C Irradiation Treatments on Rooting Performance of Pelargonium × hortorum (L.H. Bailey) Stem Cuttings - Anastasios I. Darras; Katerina Grigoropoulou; Kallirroi Dimiza; Faisal Zulfiqar (Horticulturae, 2022)
Pelargonium × hortorum (L.H. Bailey), is a South African native ornamental plant with worldwide commercial recognition used in gardens and terraces. In the present study, we evaluated the effects of low doses of UV-C irradiation on rooting performance of P. × hortorum stem cuttings. We also tested the hypothesis that UV-C-induced ethylene production directly interacted with rooting process. Over a 40 d evaluation period, the ethylene production of the UV-C-treated stem cuttings was significantly increased. UV-C irradiation positively affected rooting performance. Rooting percentage was increased in the UV-C-irradiated stem cuttings by up to 17%, time to rooting was decreased by 15% (e.g., 5 d) and root weight increased by 17% compared to the nonirradiated controls. UV-C irradiation did not affect net CO2 assimilation (As), but it induced transpiration (E) on the 14, 20, 22 and 24 d of the evaluation period. Positive correlations were found between ethylene production and As, E, stomatal conductance (gs) and root weight, while a negative correlation was recorded between days to rooting and ethylene. UV-C hastened flower production of the cuttings, but it did not affect colour parameters. We suggest that low doses of UV-C may induce endogenous ethylene production, which at low levels, interact with other hormonal mechanisms to activate root development.